Overgrazing-induced legacy effects may permit Leymus chinensis to cope with herbivory - Guo, Fenghui; Li, Xiliang; Jimoh, Saheed Olaide; Ding, Yong; Zhang, Yong; Shi, Shangli; Hou, Xiangyang (PeerJ, 2020)
There is growing evidence that herbivory-induced legacy effects permit plants to cope with herbivory. However, herbivory-induced defense strategies in plants against grazing mammals have received little attention. To further understand the grazing-induced legacy effects on plants, we conducted a greenhouse experiment with Leymus chinensis experiencing different grazing histories. We focused on grazing-induced legacy effects on above-ground spatial avoidance and below-ground biomass allocation. Our results showed that L. chinensis collected from the continuous overgrazing plot (OG) exhibited higher performance under simulated grazing in terms of growth, cloning and colonizing ability than those collected from the 35-year no-grazing plot (NG). The enhanced adaptability of OG was attributed to increased above-ground spatial avoidance, which was mediated by larger leaf angle and shorter height (reduced vertical height and increased leaf angle contributed to the above-ground spatial avoidance at a lower herbivory stubble height, while reduced tiller natural height contributed to above-ground spatial avoidance at a higher herbivory stubble height). Contrary to our prediction, OG pre-allocated less biomass to the rhizome, which does not benefit the herbivory tolerance and avoidance of L. chinensis; however, this also may reflect a tolerance strategy where reduced allocation to rhizomes is associated with increased production of ramets.
Keywords: Overgrazing; Legacy effects; Defense strategy; Leymus chinensis; Spatial avoidance; Biomass allocation